Lack of in vitro efficacy of oral forms of certain cephalosporins, erythromycin, and oxacillin against Pasteurella multocida. - Goldstein, E J (1988)
The in vitro susceptibility of human isolates of Pasteurella multocida to oral antimicrobial agents from our current study and from a review of the literature suggests that dicloxacillin (oxacillin), erythromycin, clindamycin, cephalexin, cefaclor, and cefadroxil should not be used for empiric therapy of animal bite wounds. Agents that were consistently active against P. multocida were penicillin, ampicillin, amoxicillin-clavulanic acid, tetracycline, minocycline, chloramphenicol, trimethoprim-sulfamethoxazole, and cefuroxime. Possible reasons for the confusion regarding the activity of oral cephalosporins are addressed.